Gambaran Xerostomia pada Pasien yang Menjalani Hemodialisis di Rumah Sakit Umum Daerah Undata Palu - I Ketut Sudiana; Alfrida Semuel Rabung; Laily Hidayati (FORIKES, 2019)
Introduction: CKD patients with regular hemodialysis at the Undata Palu Regional General Hospital were also found to have xerostomia. Aims: To identify xerostomia, salivary flow rate and salivary pH in patients undergo hemodialysis in RSUD Undata, Palu. Methods: Fifty patients who undergo hemodialysis were included for a cross-sectional study. Xerostomia was assessed by the Summated Xerostomia Inventory-Dutch version (SXI-D), salivary flow rate used spitting method and salivary pH used pH strips paper. Data were analyzed by descriptive analysis. Results: Based on the characteristics of respondents who experienced xerostomia, the majority were 46-56 years old, male sex, worked as IRT and PNS, had basic to secondary education and used special medicine and xerostomia were in the moderate to severe category, mean saliva flow rate of 6 ml/minute while the saliva pH is at pH 6. Conclusion: In this study found in patients undergo hemodialysis experienced xerostomia characterized by a decrease in the flow rate of saliva which also caused a decrease in salivary pH. Keywords: xerostomia; salivary flow rate;salivary pH;hemodialysis ABSTRAK Pendahuluan: Pasien PGK dengan hemodialisis teratur di Rumah Sakit Umum Daerah Undata Palu juga ditemukan mengalami xerostomia. Tujuan: untuk mengidentifikasi xerostomia, laju aliran saliva dan pH saliva pada pasien yang menjalani hemodialisis di RSUD Undata Palu. Metode: Lima puluh pasien yang menjalani hemodialisis dilibatkan pada penelitian cross-sectional. Xerostomia dinilai dengan Summated Xerostomia Inventory-Dutch version (SXI-D), laju aliran saliva menggunakan metode spitting dan pH saliva menggunakan kertas strip pH. Data dianalisis menggunakan analisis deskriptif. Hasil: berdasarkan karakteristik responden yang mengalami xerostomia mayoritas berusia 46-56 tahun, berjenis kelamin laki-laki, bekerja sebagai IRT dan PNS, berpendidikan dasar sampai menengah dan menggunakan obat tertentu serta xerostomia berada pada kategori sedang sampai parah, rerata laju aliran saliva 6 ml/menit sedangkan pH aliva berada pada pH 6. Kesimpulan: Mayoritas pasien yang menjalani hemodialisis mengalami xerostomia, penurunan laju aliran saliva dan penurunan pH saliva menjadi asam. Kata kunci: xerostomia; laju aliran saliva; pH saliva; hemodialisis